Evaluation of air‐particle abrasion of Y‐TZP with different particles using microstructural analysis. (28th May 2013) - Turp, V; Sen, D; Tuncelli, B; Goller, G; Özcan, M
Abstract Background This study evaluated the effect of air‐particle abrasion with different particle sizes on the surface roughness and phase transformation of yttria‐stabilized tetragonal zirconia ceramics (Y‐TZP). Methods Eighty‐four Y‐TZP discs of 15 mm diameter and 1.0 mm thickness were fabricated. The samples were divided into four groups (n = 21): (1) air‐particle abrasion with 30 μm CoJet sand blast coating agent (CoJet, 3M ESPE); (2) 50 μm Al2O3 particles; (3) 110 μm Al2O3 particles; and (4) 250 μm Al2O3 particles. Each group was further divided into three subgroups each (n = 7) and treated for 5 seconds, 15 seconds and 30 seconds. Mean surface roughness was determined using a profilometer. The surfaces were analysed with a scanning electron microscope. XRD analysis was employed and the relative amount of the monoclinic phase was calculated. The results were statistically analysed by two‐way analysis of variance (ANOVA, p < 0.05). Results Air‐particle abrasion with 250 μm Al2O3 particles for 30 seconds had the highest surface roughness (p < 0.001) and a significantly higher amount of monoclinic phase compared to air‐particle abrasion with 30 μm, 50 μm and 110 μm particles (p < 0.001). Conclusions Duration and particle size of air‐particle abrasion affects the roughness and phase transformation of Y‐TZP. Longer treatment times with larger particles may result in degradation of material.